Unapologetically faith based: The nature of donor engagement in the context of South African faith-based organisations - Toit, Nadine F. Bowers du (HTS teologiese studies, 2019)
The funding of faith-based organisations (FBOs) is often complex and at times unsustainable because of many factors that may render the FBO and its valuable work in serving the most marginalised vulnerable to fickle donor funding. Not least amongst such factors are that of the ‘faith factor’ – namely, the ways in which the religious dimension of an FBO works – which may be seen as too religious for secular donors such as corporates, government and other international funders. While there is a growing body of literature concerning the effects of donor funding on the work of FBOs, there has been no empirical study conducted in South Africa that specifically explores the issue of donor funding and relationships. This article, therefore, seeks to explore the nature of donor funding in South Africa with regard to the FBO sector, its challenges, sustainability and the role of faith identity regarding the relationship between donors and FBOs.